PENGARUH RASIO LIKUIDITAS, LEVERAGE, DAN SALES GROWTH TRHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Irma Susanti (JURNAL ILMIAH EDUNOMIKA, 2021)
Financial distress is a stage of decline in financial conditions that occurs before bankruptcy occurs. This study aims to examine the effect of liquidity, leverage, and sales growth on financial distress in property and real estate companies listed on the Indonesia Stock Exchange (IDX). The population in this study were all property and real estate companies listed on the Indonesia Stock Exchange for the period 2015-2019. The sample was selected based on the purposive sampling method, in order to obtain a sample of 24 companies. The data analysis technique used is logistic regression analysis, with data processing using the SPSS program. The results showed that (1) liquidity as measured by (CR) had a positive and insignificant effect on financial distress; (2) leverage as measured by (DER) has a negative and insignificant effect on financial distress; and (3) Sales Growth as measured by (GROWTH) has a positive and insignificant effect on financial distress. Keyword: Liquiditys, Leverae, Sales Growth, Financial Distress